Legalizing Gender and Equality: Courts, Markets and Unequal Pay for Women in America - Knopf, Paula (Relations industrielles / Industrial Relations, 2000)
The article reviews the book, " Legalizing Gender and Equality: Courts, Markets and Unequal Pay for Women in America," by Robert L. Nelson and William P. Bridges
Keywords: Book reviews; Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Equal pay for equal work; Labor Unions; Labor law; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z